(untitled) (Research, Society and Development, 2021)
In this work, the precursor (P)MCM-22 was prepared using the hydrothermal method in a static system and thermal modifications, delamination and acidification were carried out. This study aims to optimize the modification that promotes the disorganization of the zeolitic precursor lamellae and makes the active sites more accessible. The precursor (P)MCM-22 was prepared under hydrothermal conditions with a temperature of 150 oC and a crystallization time of 7 days. The delamination process was carried out via swelling of the lamellar precursor with CTABr and subsequent exfoliation by sonication. Characterization techniques such as X-ray diffraction, Chemical analysis by Energy Dispersive X-Ray Spectroscopy and Physical Nitrogen Adsorption were used. It was observed by the XRD analysis of the products of the syntheses carried out, that the presence of the CTABr surfactant promotes the disorganization of the lamellae. It is also concluded that there was an influence of acidification on the properties of the final products.